2014
DOI: 10.1002/lary.24716
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic gentamicin as a treatment for drop attacks in patients with Meniere's disease

Abstract: Intratympanic gentamicin treatment appears to be a long-lasting and effective treatment for MD with DAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 15 publications
1
20
0
7
Order By: Relevance
“…VOR gain measured in this way is a global measure of the whole response to a head turn, and as such, it cannot show the fine detail of the time series of the response which may reflect the way in which the sustained and transient systems are combined. Fortuitously, an answer about how these systems work may be provided by the therapeutic treatment of patients with Meniere’s disease by the use of intratympanic injections of gentamicin (ITG) (107111). …”
Section: Sustained and Transient Aspects Of Behavioral Responsesmentioning
confidence: 99%
“…VOR gain measured in this way is a global measure of the whole response to a head turn, and as such, it cannot show the fine detail of the time series of the response which may reflect the way in which the sustained and transient systems are combined. Fortuitously, an answer about how these systems work may be provided by the therapeutic treatment of patients with Meniere’s disease by the use of intratympanic injections of gentamicin (ITG) (107111). …”
Section: Sustained and Transient Aspects Of Behavioral Responsesmentioning
confidence: 99%
“…ITG, as a destructive treatment, could achieve success rates ranging from 60% to 100% in controlling MD-related DA. [10,18] Since both ITG and ITD are well-established treatment for MD, we are led to speculate that ITD may also be used for controlling MD- or DEH-related DA. ITD, free of inner ear toxicity, may attain a compromise between vertigo control and hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our results and previous findings suggested that, ITG, as a more long-lasting and effective alternative, can serve as a subsequent treatment if repeated ITD fails to effectively relieve MD-related DA. [10,19] Although the DA control rate of ITD was not as high as that of ITG, ITD, as a conservative and nondestructive procedure, can not only effectively control DA but also avoid post-ITG hearing loss and disequilibrium associated with use of gentamicin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations